Mindfulness meditation for younger breast cancer survivors: A randomized controlled trial. Issue 8 (23rd December 2014) - Bower, Julienne E.; Crosswell, Alexandra D.; Stanton, Annette L.; Crespi, Catherine M.; Winston, Diana; Arevalo, Jesusa; Ma, Jeffrey; Cole, Steve W.; Ganz, Patricia A.
<x xml:space="preserve">Abstract</x> BACKGROUND Premenopausal women diagnosed with breast cancer are at risk for psychological and behavioral disturbances after cancer treatment. Targeted interventions are needed to address the needs of this vulnerable group. METHODS This randomized trial provided the first evaluation of a brief, mindfulness‐based intervention for younger breast cancer survivors designed to reduce stress, depression, and inflammatory activity. Women diagnosed with early stage breast cancer at or before age 50 who had completed cancer treatment were randomly assigned to a 6‐week Mindful Awareness Practices (MAPS) intervention group (n = 39) or to a wait‐list control group (n = 32). Participants completed questionnaires before and after the intervention to assess stress and depressive symptoms (primary outcomes) as well as physical symptoms, cancer‐related distress, and positive outcomes. Blood samples were collected to examine genomic and circulating markers of inflammation. Participants also completed questionnaires at a 3‐month follow‐up assessment. RESULTS In linear mixed models, the MAPS intervention led to significant reductions in perceived stress (P = .004) and marginal reductions in depressive symptoms (P = .094), as well as significant reductions in proinflammatory gene expression (P = .009) and inflammatory signaling (P = .001) at postintervention. Improvements in secondary outcomes included reduced fatigue, sleep disturbance, and vasomotor symptoms and increased peace and meaning and positive affect (P < .05 for all). Intervention effects on psychological and behavioral measures were not maintained at the 3‐month follow‐up assessment, although reductions in cancer‐related distress were observed at that assessment. CONCLUSIONS A brief, mindfulness‐based intervention demonstrated preliminary short‐term efficacy in reducing stress, behavioral symptoms, and proinflammatory signaling in younger breast cancer survivors. Cancer 2015;121:1231–1240. © 2014 American Cancer Society.